Study of Functional and Chemical Properties of Red Bean (Phaseolus vulgaris L.) Sprouts Flour - Wisaniyasa, Ni Wayan; Suter, I Ketut (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 3 No 1 (2016), 2016)
The purpose of this study was to determine functional and chemical properties of red bean (Phaseolus vulgaris L.) sprouts flour. The design used was Completely  Randomized Design with three  replications. The results showed that the germination of red beans for 2 days did not affect the functional properties of flour. Functional properties of red bean sprouts flour are: water absorption capacity of 145.35%, oil absorption capacity of 89.84%, swelling power of 3.06 g/g, and solubility of 22.30%. Germination process affect the chemical properties of sprouts flour, which is capable of increasing the ash content, protein content, antioxidant capacity, and dietary fiber but  lower levels of antitrypsin activity, whereas no effect on water content, fat and carbohydrates content. Chemical properties of red bean sprout flour is water content of 6.84%, ash content of 4.53%, protein content of 17.59%, fat content of 6.22%, carbohydrate of 64.82%, antioxidant capacity 140,34 mg/Kg,  dietary fiber of 32.23%  and antitrypsin activity of 2983.59 mg/g sample.
Keywords: functional; chemical; properties; bean sprouts; flour